2015
DOI: 10.11621/pir.2015.0112
|View full text |Cite
|
Sign up to set email alerts
|

The genesis of vandalism: From childhood to adolescence

Abstract: This study was developed because vandal behavior is an increasing threat in the world. Countries, commercial companies, and individuals experience great damage to property as a result of individual vandal acts. In addition, vandalism threatens not only "tangible assets" but also the cultural and historical heritage of modern humanity. Despite the threatening spread of vandalism, the study of its psychological foundations, including its origins, in the context of individual life courses is in many ways terra in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…We suppose that a substantial part of the children may have already formed a 'subject-object' interaction strategy, as they performed not random acts of vandalism, but repeated them over and over again. This statement is confirmed by the results of the analysis of vandal behaviour among primary school children: the teachers' expert assessment showed that at least 10% of the pupils demonstrate vandal behaviour systematically (VOROBYEVA et al 2015). They often break toys and other objects for different reasons: from 'spontaneous splashes of negative emotions' to 'focusing on the destruction or damage in order to achieve some personal goals'.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…We suppose that a substantial part of the children may have already formed a 'subject-object' interaction strategy, as they performed not random acts of vandalism, but repeated them over and over again. This statement is confirmed by the results of the analysis of vandal behaviour among primary school children: the teachers' expert assessment showed that at least 10% of the pupils demonstrate vandal behaviour systematically (VOROBYEVA et al 2015). They often break toys and other objects for different reasons: from 'spontaneous splashes of negative emotions' to 'focusing on the destruction or damage in order to achieve some personal goals'.…”
Section: Resultsmentioning
confidence: 67%
“…In compliance with the findings of the teachers' survey, nearly 27% of primary school children made destructive or transforming actions towards the school environment (VOROBYEVA et al 2015 children vandalism is a tactical action aimed at setting up relationships with the external environment. It can be a form of emotional displacement against certain forms of social influence (school discipline, homework etc.).…”
Section: Resultsmentioning
confidence: 75%
“…Vandalisme mengancam tidak hanya "aset berwujud" tetapi juga warisan budaya dan sejarah kemanusiaan modern. Sebuah studi terhadap anak-anak, remaja, dan dewasa, serta lingkungan sosial mereka, mengungkapkan mekanisme kesiapan untuk melakukan tindakan perusak yang hadir sejak kecil (Vorobyeva, Kruzhkova, and Krivoshchekova 2015).…”
Section: Pendahuluanunclassified
“…В результате диагностики 832 подростков и юношей с использованием ценностного опросника Ш. Шварца [9], ав-торского опросника «Мотивы вандального поведения» [2] нами были выделе-ны четыре специфических группы респондентов, имеющих сущностные раз-личия в структуре и содержании системы ценностных ориентаций.…”
Section: теоретико-эмпирические основы проектирования моделиunclassified